Acute hemodynamic effects of iatrogenic inter-atrial shunts after percutaneous edge-to-edge mitral valve repair. (25th November 2020) - Koschutnik, M; Goliasch, G; Nitsche, C; Kammerlander, A.A; Dona, C; Dannenberg, V; Schneider, M; Bartko, P; Mora, B; Bartunek, A; Andreas, M; Hengstenberg, C; et al.
Abstract: Background: Implantable interatrial shunt devices improve pulmonary vascular function in patients with heart failure by transferring richly oxygenated blood to the right heart. Whether iatrogenic atrial septum defects (iASDs) after percutaneous edge-to-edge mitral valve repair (pMVR) are also associated with beneficial hemodynamic effects has not been investigated. Methods: We consecutively enrolled patients with relevant functional (FMR) and degenerative mitral regurgitation (DMR) scheduled for pMVR. Invasive hemodynamic assessments were performed prior to and immediately after the procedure. Results: 97 consecutive patients (75.4±9.1 years; 58% female) were prospectively included, 65 (66%) presented with relevant FMR. At baseline when compared to the DMR group, FMR was associated with worse left ventricular (LV) function (LV ejection fraction: 39 vs. 49%; p=0.001), higher NT-proBNP levels (7404 vs. 5214 pg/mL; p=0.023), worse renal function (serum creatinine: 1.7 vs. 1.3 mg/dL; p=0.019), and higher usage of spironolactone (68 vs. 42%; p=0.018) and sacubitril/valsartan (33 vs. 0%; p<0.001). Following pMVR, cardiac output (CO) and systemic blood flow (Qs) increased significantly (CO: 4.6 to 5.5 L/min; p<0.001; Qs: 4.9 to 5.8 L/min; p=0.002), with more pronounced changes in the FMR subgroup (ΔCO: 1.0 vs. 0.6 L/min; Figure 1A; ΔQs: 1.2 vs. 0.1 L/min), when compared to DMR. Pulmonary blood flow (Qp) increased by 26% (4.3 to 5.4 L/min; p=0.008), accompanied by a raise in pulmonary artery (PA) oxygen (O2) saturation from 73 to 77% (p<0.001). Arterial O2 saturation levels remained unchanged (98.3 to 98.7%; p=0.165), confirming no significant changes in systemic oxygenation. These changes were associated with a slight decline in pulmonary vascular resistance (PVR: 250 to 225 dynes*sec/cm5; p=0.369, Figure 1B), and a tendency towards improvement of pulmonary compliance (PAC: 3.6 to 4.0 mL/mmHg; p=0.414). Conclusions: Invasively measured CO, Qs, Qp, and mixed-venous PA O2 saturation increased immediately after pMVR, alongside with potentially beneficial effects on pulmonary vasculature with marked improvements in PVR and PAC. These changes were more pronounced in the FMR subgroup. Further studies are required to assess long-term hemodynamic effects and underlying mechanisms of persistent iASDs on pulmonary vascular function. Funding Acknowledgement: Type of funding source: None